A Novel Manganese(II) MOCVD Precursor: Synthesis, Characterization, and Mass Transport Properties of Mn(hfa)2tmeda1. Issue 1 (18th February 2013) - Lipani, Zaira; Catalano, Maria R.; Rossi, Patrizia; Paoli, Paola; Malandrino, Graziella
Abstract The complex, Mn(hfa)2tmeda [(H‐hfa = 1, 1, 1, 5, 5, 5‐hexafluoro‐2, 4‐pentandione, tmeda = N, N, N′, N′‐tetramethylethylendiamine)], is synthesized in a single‐step reaction and characterized by elemental analysis, thermal analysis, and infrared (IR) spectroscopy. The solid‐state crystal structure of Mn(hfa)2tmeda provides evidence of a mononuclear structure. The thermal analyses show that the complex is thermally stable and can be evaporated to leave less than 2% residue. The complex properties are compared with the first generation, commercially available MnII and MnIII precursors, Mn(acac)2 (Hacac = acetylacetone) and Mn(tmhd)3 (Htmhd = 2, 2, 6, 6‐tetramethyl‐3, 5‐heptanedione), respectively. Mn(hfa)2tmeda represents the first example of manganese(II) precursor that can be used in the liquid phase without decomposition, thus providing constant evaporation rates, even for long deposition times. It is successfully applied to the reduced‐pressure, metal‐organic (MO)CVD of the Mn3O4 phase.